ANALISIS KUALITAS SUMBER DAYA MANUSIA DALAM PERILAKU KEUANGAN IBU RUMAH TANGGA LINGKUNGAN PERUMNAS PATRANG KOTA JEMBER DI ERA DIGITALISASI - Pramesthi, Riska Ayu; Karnadi, Karnadi (Relawan Jurnal Indonesia, 2023)
The quality of human resources in the financial behavior of housewives in the era of digitalization, the existence of digital media (market place) and free online loan applications, makes housewives unable to control their household's financial behavior which leads to various problems such as money running out prematurely. , do not have regular savings in the form of saving money or in financial institutions, and do not have an emergency fund. In fact, it is not uncommon to find many family members who are in debt or borrow money from banks, neighbors or from agents where money is borrowed. The aim of this research is to determine and analyze the management of the quality of human resources in the financial behavior of housewives in the Perumnas Patrang Environment, Jember City. The method in this research uses a qualitative approach with a survey type. Data collection in research uses observation and interviews. The findings obtained from the lack of knowledge about financial management among housewives will have an impact on the economy of the perpetrators, especially in the current era of digitalization.